The process of regionalization in the Asia-Pacific region: the current geopolitical and international legal trends (International relations and international law Journal, 2016)
This paper examines the status quo, and the processes of regionalization in the Asia-Pacific region in the context of state protection of the collective interests of the States Parties. The main attention is paid to the analysis of military-political situation in the region, the nature and prospects of which depends not only on the security of the individual actors, but also in the whole region-wide stability. The authors in this regard an attempt to formulate some theoretical and practical approaches to resolve existing problems.
Keywords: Asia-Pacific region; collective security; regionalism; military-political aspect; international organizations